Neuroendocrine Control of Macrophage Development and Function - Jurberg, Arnon Dias; Cotta-de-Almeida, Vinícius; Temerozo, Jairo Ramos; Savino, Wilson; Bou-Habib, Dumith Chequer; Riederer, Ingo (Frontiers in Immunology, 2018)
Macrophages carry out numerous physiological activities that are essential for both systemic and local homeostasis, as well as innate and adaptive immune responses. Their biology is intricately regulated by hormones, neuropeptides and neurotransmitters, establishing distinct neuroendocrine axes. The control is pleiotropic, including maturation of bone marrow-derived myeloid precursors, cell differentiation into functional subpopulations, cytotoxic activity, phagocytosis, production of inflammatory mediators, antigen presentation and activation of effector lymphocytes. Additionally, neuroendocrine components modulate macrophage ability to influence tumor growth and to prevent the spreading of infective agents. Interestingly, macrophage-derived factors enhance glucocorticoid production through the stimulation of the hypothalamic-pituitary-adrenal (HPA) axis. These bidirectional effects highlight a tightly controlled balance between neuroendocrine stimuli and macrophage function in the development of innate and adaptive immune responses. Herein we discuss how components of neuroendocrine axes impact on macrophage development and function, and may ultimately influence inflammation, tissue repair, infection or cancer progression. The knowledge of the crosstalk between macrophages and endocrine or brain-derived components may contribute to improve and create new approaches with clinical relevance in homeostatic or pathological conditions.